The Impact of Work Life Balance and Employee Engagement on Employee Performance with Job Satisfaction as an Intervening Variable (Case Study Of Employees of PT. Hagihara Westjava Industries) - Andini Putri Kinanti; Novi Fitria Hermiati (Jurnal Ilmu Manajemen Profitability, 2023)
This Good performance is a step to achieve company goals and therefore must be planned properly. In this study, researchers will prove whether work life balance and employee engagement can affect an employee's performance on job satisfaction as an intervening variable. Quantitative method was used in this research. The population in this study are office staff employees of PT. Hagihara Westjava Industries numbered 100 people. Researchers used probability sampling technique with random sampling as the type of sample. The method used in this study is Structural Equation Modeling (SEM) Analysis by Lisrel software version 8.80. The gains in this study are that Work Life Balance has no significant impact on Employee Performance, Employee Engagement has no significant impact on Employee Performance, Work Life Balance has a significant positive impact on Job Satisfaction, Employee Engagement has no significant effect on Job Satisfaction, Job Satisfaction has a positive and significant impact on Employee Performance, Job Satisfaction can mediate the effect of Work Life Balance on Employee Performance, and Job Satisfaction is able to mediate the effect of Employee Engagement on Employee Performance.